Adaptação e validação da escala de dependência de exercício físico em versão tradicional e informatizada - Oliveira, Isabel Cristina Vasconcelos de (2010)
While providing physical and psychological benefits, excessive exercise could be or cause a compulsive behavior, making the individual dependent on it. In a parallel discussion, computerized psychological instruments, for a hand, reflects the development of information technology and your applicability to other areas, but also shows little advance for Psychological Assessment. In this perspective, this study aims to adapt the Exercise Dependence Scale (EDS-R) in two formats (paper-and-pencil and computerized) and evaluate evidence of factorial and convergent validity, and reliability of each version and compare them with each other. It is also proposed to observe the relationship of some bio-demographic (Sex, age, frequency, duration and intensity of practice exercise) and the exercise dependence (DEF). For this purpose, 709 regular physical activity practitioners, selected by procedures non-probabilistic sampling, responded a adapted version of EDS-R, Muscle Appearance Satisfaction Scale (MASS), Body Modification Scale (BMS) and a demographic questionnaire, analyzed through Exploratory Factor Analysis, Cronbach's Alpha and not parametric tests. Both the traditional version and the computer showed a seven factors structure, explaining 57 and 62% of the variance, respectively, and Cronbach's alphas of 0.83 and 0.89. Factors were: (1) intentionality, (2) continuity, (3) tolerance, (4) reduction of other activities, (5) lack of control, (6) abstinence and (7) time spent on exercise. Relationships were observed between the Exercise Dependence and the variables: age, diets, consumption of food supplements and medicines for weight change, desire to do plastic surgery and body satisfaction. We observed also a positive correlation between the DEF and the frequency, duration and intensity of exercise, and the factor "Dependence on exercising" from MASS, indicating convergent validity of the EDS-R. Finally, comparisons between the two formats were equivalent, with few changes: computerized version achieved higher DEF scores. Based on these results, it can be concluded that the EDS-R has factorial and convergent validity, reliability, to measure exerceise dependence on traditional e computerized formats. DEF is related to actions used to body modification and behaviors toward exercise. Finally, it was found equivalence between the formats, especially in psychometric parameters, thus suggesting feasibility of a computerized assessment. However, it was observed that the computerized data has sample recruiting strategies more limited